Enhanced pyroelectric response from domain-engineered lead-free (K0.5Bi0.5TiO3-BaTiO3)-Na0.5Bi0.5TiO3 ferroelectric ceramics. Issue 4 (April 2021) - Thakre, Atul; Maurya, Deepam; Kim, Do Yoen; Kim, Yunseok; Sriboriboon, Panithan; Yoo, Il-Ryeol; Priya, Shashank; Cho, Kyung-Hoon; Song, Hyun-Cheol; Ryu, Jungho
Abstract: Enhanced pyroelectric response is achieved via domain engineering from [001] grain-oriented, tetragonal-phase, lead-free 0.2(2/3K0.5 Bi0.5 TiO3 -1/3BaTiO3 )-0.8Na0.5 Bi0.5 TiO3 (KBT-BT-NBT) ceramics prepared by a templated grain growth method. The [001] crystallographic orientation leads to large polarization in tetragonal symmetry; therefore, texturing along this direction is employed to enhance the pyroelectricity. X-ray diffraction analysis revealed a Lotgering factor (degree of texturing) of 93 % along the [001] crystallographic direction. The textured KBT-BT-NBT lead-free ceramics showed comparable pyroelectric figures of merit to those of lead-based ferroelectric materials at room temperature (RT). In addition to the enhanced pyroelectric response at RT, an enormous enhancement in the pyroelectric response (from 1750 to 90, 900 μC m −2 K −1 ) was achieved at the depolarization temperature because of the sharp ferroelectric to antiferroelectric phase transition owing to coherent 180° domain switching. These results will motivate the development of a wide range of lead-free pyroelectric devices, such as thermal sensors and infra-red detectors.